Natural Occurrence of Fusarium Mycotoxins (Fumonisins, Zearalenone and T-2 toxin) in Corn for Human Consumption in Yemen - Al-Jobory, Hala J.; Mahmoud, Ahmed L. E.; Al-Mahdi, Abdullah Y. (PSM Microbiology, 2017)
The presence of fumonisins, zearalenone (ZEA) and T-2 toxin has not been regulated in the legislation of Republic of Yemen. Therefore, the data on contamination of cereals, especially corn, which is highly susceptible to contamination by such toxins, are not sufficient. In this regard, fifty corn kernels which showed Fusarium contamination and which were obtained from different corn growing areas in Yemen (Ibb, Taiz, Thamar, Sana’a and Al-Hodaida), during the spring- summer (2010 – 2011 and 2011 – 2012) cycles, were further analyzed for the presence of these toxins using thin layer chromatography (TLC) and enzyme linked immunosorbent assay (ELISA) techniques. 72% of samples were contaminated with fumonisins with concentrations ranging from 00.57 to 120.20 µg/g with an average of 9.33 µg/g , 30% were contaminated with ZEA with concentrations ranging from 00.17-03.30 µg/g with an average of 01.04 µg/g, while all samples were T-2 toxin free. The co-occurrence of fumonisins and ZEA was also detected in 15 samples (30%). This study is considered the first preliminary survey dealing with three occurring mycotoxins naturally in fresh corn in Yemen. Thus, may be used as a base for further studies assessment for other cereals as well. And in terms of fumonisins and ZEA these high levels detected do not only cause overt mycotoxicosis but also leads to the impairment of immune and acquired resistance to infections causing health problems which lead to economic losses.